Extracting flavonoid from Ginkgo biloba using lignocellulolytic bacteria Paenarthrobacter sp. and optimized via response surface methodology. (21st March 2021) - Han, Sihai; Chio, Chonlong; Ma, Tianxiao; Mokale Kognou, Aristide Laurel; Shrestha, Sarita; Chen, Feifei; Qin, Wensheng
Abstract: Ginkgo biloba flavonoids are important natural bioactive compounds with strong physiological effects. To develop an eco‐friendly and effective method for extracting flavonoids from plants, a microbial method involving lignocellulose‐degrading bacterial enzymes was developed to improve flavonoid extraction from Ginkgo biloba leaves. In this study, a newly isolated bacterial strain, Paenarthrobacter sp. S1.3, was employed for the fermentation processing of Ginkgo biloba leaf powder. The enzymatic characteristics of xylanase, CMCase, polygalacturonase, and β ‐glucosidase from Paenarthrobacter sp. S1.3 were also investigated. The major fermentation parameters for the microbial extraction of Ginkgo biloba flavonoids were optimized using response surface methodology. Under optimal conditions (30.6 °C, initial pH 7.6, and fermentation time 25 h), a total flavonoid yield of 34.15 ± 0.52 mg g −1 dry weight was obtained, which was 2.11 fold and 1.42 fold higher than the yields obtained from the unfermented and ethanol extraction methods, respectively. The optimized results also suggest that the polygalacturonase and β ‐glucosidase might play an important role in flavonoid extraction. Fermentation utilizing lignocellulose‐degrading bacteria was a feasible green approach to improve the extraction of natural compounds from plants. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd